A new species of Oxalis L. (Section Ionoxalis Small, Oxalidaceae) from northern Michoacan, Mexico - Pérez-Calix, Emmanuel (Instituto de Ecología, A.C., 2009)
Oxalis morelosii is proposed as a new species, described, and illustrated. It is based on plants from the southern portion of the municipality of Morelia, Michoacán, an area to which this species is microendemic. The new taxon belongs to section Ionoxalis and is similar to O. alpina (Rose) Knuth, O. galeotii Turcz., O. gregaria (Rose) Knuth, O. jacquiniana H.B.K. y O. lunulata Zucc., all of which have 3-foliate leaves and 3-nerved scales on the bulbs. A dichotomous key is provided to help separate the new species from these others.